Процедура бізнес-планування та її вплив на розвиток малого бізнесу - Черевко, О.Л.; Іванісова, А.В.; Гарькава, Т.Л. (Культура народов Причерноморья, 2013)
У статті розглянуто сутність бізнес-планування як інструменту залучення інвестицій та
стабілізації господарської діяльності підприємств. Висвітлено особливості процедури бізнес-планування
в Україні та зарубіжних країнах, досліджено стан активності суб’єктів малого бізнесу в Україні,
розкриті основні проблеми малого підприємництва. З’ясовано, яким чином процедура бізнес-планування
зменшує ризики малого бізнесу та сприяє його розвитку. Обґрунтовано доцільність впровадження
бізнес-плану як обов’язкового документа у господарській діяльності підприємств. В статье рассмотрена сущность бизнес-планирования как инструмента привлечения
инвестиций и стабилизации хозяйственной деятельности предприятий. Освещены особенности
процедуры бизнес-планирования в Украине и зарубежных странах, исследовано состояние активности
субъектов малого бизнеса в Украине, раскрыты основные проблемы малого предпринимательства.
Выяснено, каким образом процедура бизнес-планирования уменьшает риски малого бизнеса и
способствует его развитию. Обоснована целесообразность внедрения бизнес-плана как обязательного
документа в хозяйственной деятельности предприятий. The article reviews nature of business planning as an instrument of attracting investment and
stabilize economic activity. The specific features of the business-planning process in Ukraine and foreign
countries, examines the state of small business activity in Ukraine. Determined that the most organic structural
elements of the market economy is small business. Small businesses provide the flexibility and stability of the
economic system. This article deals with the basic problems of small businesses, because it is extremely
vulnerable to environmental effects. It is shown how the process of business planning reduces the risk of small
business and contributes to its development. The necessity of implementing the business plan as a binding
instrument in economic activity. With the development of the business plan of a small business future leaders can
learn the fundamental prospects of the company; choose the correct strategy and tactics to achieve their goals,
anticipate possible changes in the market and find a way out of possible crisis situations. The article notes that
in our time developing quality business plan is the key to the survival of small businesses. Binding of the
business planning contributes to the revitalization of small businesses, which in turn leads to an increase in
GDP, increase revenue, of new jobs and the economy as a whole.